Assessing input-specific knowledge gaps in farmers' demand for agricultural inputs - Seed and irrigation technologies in Nigeria - Takeshima, Hiroyuki (Academic Journals, 2011)
In Sub-Sahara African countries like Nigeria where the substitutability of agricultural inputs tend to be low, policies that directly improve access to deficient inputs (“input-specific” policies) may be more effective than other policies that improve access to all inputs but to a lesser extent (“general” policies). This study uniquely assesses how input-specific policies were distinguished from general policies among selected studies on seed and irrigation technologies in Nigeria. Findings indicate that significant knowledge gaps might exist in Nigeria for “input-specific” information and in different ways for each seed and irrigation technologies. Key implications on future research were discussed.